Potrayal of Post-Traumatic Stress Diorder Among Flood Survivors - Zakiah, Ernita; Rosalinda, Irma; Mauna, Mauna (Journal of Research and Measurement in Psychology: JPPP, 2021)
This study aims to look at the description of post traumatic stress disorder (PTSD) in flood survivors. Data method using PCL-C measuring instrument. This study used the PCL-C scale from Weathers et al., (1994) developed by Solichah (2007). Data analysis was performed using descriptive analysis techniques with the help of SPSS version 22. Based on the results of the analysis, it was found that subjects who experienced symptoms of post-traumatic stress disorder (PTSD) who were in the high category were 24.6%, 61.5% moderate, and low 13,8%.